Mature results of a prospective study of deintensified chemoradiotherapy for low‐risk human papillomavirus‐associated oropharyngeal squamous cell carcinoma. Issue 11 (26th March 2018) - Chera, Bhishamjit S.; Amdur, Robert J.; Tepper, Joel E.; Tan, Xianming; Weiss, Jared; Grilley‐Olson, Juneko E.; Hayes, D. Neil; Zanation, Adam; Hackman, Trevor G.; Patel, Samip; Sheets, Nathan; Weissler, Mark C.; et al.
Abstract : BACKGROUND: The purpose of the current study was to determine quality of life and tumor control from a prospective phase 2 clinical trial evaluating deintensified chemoradiotherapy for favorable risk, human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma. METHODS: Patients with T0‐T3, N0‐N2c, M0, p16‐positive disease and a minimal smoking history were treated with 60 grays of intensity‐modulated radiotherapy with concurrent weekly intravenous cisplatin (30 mg/m 2 ). The primary study endpoint was the pathologic complete response rate based on biopsy of the primary site and dissection of pretreatment positive lymph node regions. The pathologic complete response rate as previously reported was 86%. Herein, the authors report secondary endpoint measures of local control, regional control, cause‐specific survival, distant metastasis‐free survival, and overall survival, and patient‐reported outcomes (European Organization for Research and Treatment of Cancer [EORTC] Quality of Life Questionnaire [EORTC QLQ‐C30] and the Patient‐Reported Outcomes version of Common Terminology Criteria for Adverse Events [PRO‐CTCAE]). RESULTS: A total of 44 patients enrolled with a median follow‐up of 36 months (88% with ≥2 years). The 3‐year local control, regional control, cause‐specific survival, distant metastasis‐free survival, and overall survival rates were 100%, 100%, 100%, 100%, and 95%, respectively. The mean before and 3‐year after EORTC QOL scores were: global: 80 of 78; swallowing: 11 of 11; dry mouth: 16 of 41; and sticky saliva: 6 of 29. The mean before and 3‐year after PRO‐CTCAE scores were: swallowing: 0.4 of 0.7; and dry mouth: 0.4 of 1.4. Approximately 39% of patients required a feeding tube (median duration, 15 weeks; none were permanent). There were no ≥grade 3 late adverse events reported. CONCLUSIONS: For patients with favorable‐risk human papillomavirus‐associated oropharyngeal squamous cell carcinoma, a substantially decreased intensity of therapy with 60 grays of intensity‐modulated radiotherapy and weekly low‐dose cisplatin produced better preservation of quality of life compared with standard therapies while maintaining excellent 3‐year tumor control and survival. Cancer 2018;124:2347‐54 . © 2018 American Cancer Society . Abstract : In the current study, a substantially decreased intensity of therapy with 60 grays of intensity‐modulated radiotherapy is studied among patients with favorable risk human papillomavirus‐associated oropharyngeal squamous cell carcinoma. The deintensified chemoradiotherapy regimen produces better preservation of quality of life compared with standard therapies while maintaining excellent 3‐year tumor control and survival.